Antioxidant, Hepatoprotective and Antiatherogenic Effects of Curcumin on High Fat Diet Induced Dyslipidemia in Rats - Khan, Nazish Iqbal; Mahboob, Tabassum (Pakistan Journal of Nutrition, 2014)
Present study is designed to investigate the atheroprotective potential of curcumin in rat models of diet induced dyslipidemia. Twenty four wistar rats of same age and sex were selected for the study and divided into four experimental groups with six animals per group. Group I was control untreated rats, group II rats received high fat diet for eight weeks, group III received 0.2 g/kg of body weight/day curcumin together with fat diet and group IV had only curcumin administration for upto four weeks. Results showed that curcumin treatment with or without fat diet administration significantly reduce plasma lipid levels, ALT, AST, ALP and glucose concentrations. High fat diet administration significantly suppresses levels of catalase, SOD and glutathione in these tissues. Whereas MDA levels were significantly raised. Curcumin treatment improve these tissue antioxidant enzyme status together with decreased MDA levels. These results suggests that daily dietary intake of curcumin in recommended doses may be helpful in restoring lipid disorders and maintaining body’s antioxidant status in patients of cardiovascular diseases.